Awareness on data privacy vis-à-vis data management practices at a state university in Quezon province: Input towards data-driven policy and manual for good governance - Miano, Leomar C. (Edelweiss Applied Science and Technology, 2025)
This study investigated the relationship between awareness on data privacy and management practices at Southern Luzon State University (SLSU). Awareness on data privacy was gauged based on the provisions of the Data Privacy Act of 2012 (RA No. 10173) and its implementing rules and regulations, while management practices were examined using indicators such as collecting personal data, processing personal data, and sharing personal data. Through simple random selection, a survey questionnaire was distributed to SLSU staff, including teaching and non-teaching personnel. Three hundred eight (308) participants completed the survey, which was used for the data analysis using frequency, percentage, mean, t-test, ANOVA, and correlation. Based on the statistical result, in overall, the employees of SLSU previously read and somehow understood the statement of RA No. 10173 with a mean of 3.19. Moreover, the overall management practices of the employees toward data privacy were excellent. On the other hand, comparing the respondents’ awareness and management practices when grouped according to the profile, among all the categories, only length of service significantly differed in management practices. Furthermore, there is a strong correlation between university employees’ awareness of the Data Privacy Act and their data management practices, indicating that employees’ great management practices are due to their knowledge of the Data Privacy Act. This study suggests that in order to adhere to the principles of good governance, the university may utilize this result for policy and the development of a data privacy manual.